Divan by Kefeli Mustafa Müdâmî - Kol, Nilüfer. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2007., 2007)
The subject of this thesis is the Divan by Kefeli Mustafa Müdâmî, one of the sixteenth century Ottoman poets. The aim of this work is to determine and analyze the text by comparing the two manuscripts. The thesis basically consists of two parts: The first part analyzes the Divan in terms of form, such as genres of verses, rhythm, rhyme, etc.; religious, historical, mythological, geographical elements; structure and characteristics of style. The second part which gives the transcripted version of the whole text presents the critical edition of the Divan. An index exhibiting the proper names used in the Divan is appended to the end of the work. A copy of one of the original manuscripts is also added to the end. With this work, which studies the Divan by Müdâmî, especially by introducing the menakıbname section, it is intended to extend a new text to the literature of menakıbname genre narrating Emir Sultan. Furthermore it is tried to enlighten the poet’s life and literary style, who is not well-known in Old Turkish Literature.